OPERATOR WORKLOAD ANALYSIS ON TRAILER OPERATION USING TWO WHEEL TRACTOR WITH CAGE WHEEL IN PALM OIL SOIL - Muhammad Idkham; Muhammad Dhafir; Safrizal Safrizal; Safna Marisza (Jurnal Agroindustri, 2022)
The operation of the pivot trailer on flat land is more ergonomic than conventional trailers, but on sloping land it has never been tested. The operation of the two-wheeled tractor carried out by the operator on uneven land has problems with the steering handlebar which goes up and down following the movement of the tractor body, thus affecting the increase in workload. To reduce the excessive workload, it is necessary to design a trailer that can be controlled easily. The purpose of this study was to analyze ergonomics, especially the operator's workload when operating a pivot trailer and conventional trailer on a two-wheel tractor using cage wheels. The trailer is towed on a tractor with treatment on sloping land and flat land with several turns, and data collection of the operator's workload uses the heart rate method. The results showed that the operation of the pivot trailer for sloping land (0°, 10°, and 30°) respectively showed IRHR values of 1.13, 1.15, and 1.46 or work levels of "Light", "Light”, and “Medium”. When using a conventional trailer, the IRHR values are 1.12, 1.12, and 1.39 or work levels of “Light”, “Light” and “Medium”. The average energy consumption rate for operating a pivot type trailer is 2.80 kcal/hour.kg-bb (kilocalories per hour per operator weight), while using a conventional trailer is 2.75 kcal/hour.kg-bb. The level of operator workload is also influenced by skills in driving.